2005
DOI: 10.2460/ajvr.2005.66.289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac lesions and risk factors associated with myocarditis and dilated cardiomyopathy in southern sea otters (Enhydra lutris nereis)

Abstract: Cardiac disease is an important cause of death in southern sea otters. Domoic acid toxicosis and infection with S. neurona are likely to be 2 important causes of myocarditis in sea otters. Domoic acid-induced myocarditis appears to progress to DCM, and depletion of myocardial L-carnitine may play a key role in this pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 66 publications
2
54
0
Order By: Relevance
“…1). These study sites were selected based on previous work showing high otter mortality or exposure to T. gondii and S. neurona in these regions (Miller et al, 2002a;Kreuder et al, 2003;Kreuder et al, 2005;. All fresh carcasses recovered in good postmortem condition (postmortem interval ,72 hr) from the two study sites between January 1998 and December 2004, and that received a full necropsy by pathologists, were considered for inclusion in the study.…”
Section: Sea Otter Case Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). These study sites were selected based on previous work showing high otter mortality or exposure to T. gondii and S. neurona in these regions (Miller et al, 2002a;Kreuder et al, 2003;Kreuder et al, 2005;. All fresh carcasses recovered in good postmortem condition (postmortem interval ,72 hr) from the two study sites between January 1998 and December 2004, and that received a full necropsy by pathologists, were considered for inclusion in the study.…”
Section: Sea Otter Case Selectionmentioning
confidence: 99%
“…Protozoal mortality cases were selected if T. gondii or S. neurona encephalitis were identified as the primary or contributing cause of death according to the following case definition. A histopathologic diagnosis of ''protozoal encephalitis'' (PE) was defined when moderate to severe inflammation of brain tissue was observed in association with proliferating protozoa (Kreuder et al, 2003). Toxoplasma gondii mortality cases were defined based on presence of multifocal, lymphoplasmacytic protozoal encephalitis on histopathology, combined with T. gondii isolation in cell culture from brain or positive staining on immunohistochemistry (IHC; Miller et al, 2002b).…”
Section: Sea Otter Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cells were also observed in both the atrial and ventricular myocardium. 26 In contrast, however, DOM toxicity studies conducted on an exposed Californian sea lion population showed myocardial degeneration limited to the ventricles. 28 The link between DOM exposure and the reported cardiomyopathies has not as yet been characterized, and it remains to be determined whether the damage is the consequence of a direct (ie, cardiotoxic) or indirect [ie, central nervous system (CNS)/autonomic discharge] interaction.…”
mentioning
confidence: 97%
“…26,27 Cardiac lesions within a Californian sea otter population have been described to include myocardial pallor and multifocal myocardial necrosis associated with myocardial hemorrhage. Inflammatory cells were also observed in both the atrial and ventricular myocardium.…”
mentioning
confidence: 99%